Optimizing a Calorimetric Method for Quantitative Assessment of Alkaline Phosphatase to Confirm the Osteogenic Differentiation of Mesenchymal Stem Cell - Samaneh Harimi; Fatemeh Zare; Farzaneh Fesahat; Mahdieh Mondanizadeh (مجله علمی دانشگاه علوم پزشکی کردستان, 2023)
Background and Aim: Evaluation of the alkaline phosphatase expression is known as one of the diagnostic markers to confirm the stem cells differentiation into osteoblasts. Several methods, including immunocytochemistry, are used to measure alkaline phosphatase in different studies. Due to limitations of using this method, we decided to optimize the calorimetric method as an alternative, low cost and efficient method for quantitative assessment of alkaline phosphatase. Materials and Methods: Mesenchymal stem cells derived from human adipose tissue were used. Cells were differentiated into osteoblasts using an induction medium. Alkaline phosphatase levels were assessed on the days 0 and 21 of differentiation using both immunocytochemistry and calorimetric methods. Results: Immunocytochemistry findings demonstrated a significant increase (approximately 5-fold) in alkaline phosphatase expression level on the 21st day of differentiation compared to that on the day 0 (p <0.0001). Also, statistical analysis of the results of the calorimetric test showed a significant increase (approximately 9-fold) in alkaline phosphatase expression level on the 21st day of differentiation compared to  that on the day 0 (p<0.0001). Conclusion: Comparison of the data between calorimetric and immunocytochemistry showed similar results. These findings suggested that colorimetric assay can be used as an alternative, quantitative, fast, and low cost method for determining the levels of alkaline phosphatase in osteoblasts differentiated from mesenchymal stem cells.